If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.5(10p + -50) = 4(9 + -6p) Reorder the terms: 2.5(-50 + 10p) = 4(9 + -6p) (-50 * 2.5 + 10p * 2.5) = 4(9 + -6p) (-125 + 25p) = 4(9 + -6p) -125 + 25p = (9 * 4 + -6p * 4) -125 + 25p = (36 + -24p) Solving -125 + 25p = 36 + -24p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '24p' to each side of the equation. -125 + 25p + 24p = 36 + -24p + 24p Combine like terms: 25p + 24p = 49p -125 + 49p = 36 + -24p + 24p Combine like terms: -24p + 24p = 0 -125 + 49p = 36 + 0 -125 + 49p = 36 Add '125' to each side of the equation. -125 + 125 + 49p = 36 + 125 Combine like terms: -125 + 125 = 0 0 + 49p = 36 + 125 49p = 36 + 125 Combine like terms: 36 + 125 = 161 49p = 161 Divide each side by '49'. p = 3.285714286 Simplifying p = 3.285714286
| (3x+7)=2 | | 3r+3-6-4r-9+3r=2r+5-4 | | 17=14+16y | | 6u-12= | | 10(t-2)+8t=6(3t+3)-1 | | 7x-1270=-318 | | 10d-6+2=100 | | (x+11)+(x+3)=75 | | 9x-150=-51 | | -8.38v+-10.71=131.382 | | -(3p-7)=-8 | | 2x-8x+6=34 | | 5(x+2)=2(x+305) | | -22+s=38 | | 2(5w+15)-1w+1=3+3w | | 4y-5-2y=4 | | (x+11)+(x+3)= | | -13+2x^2-1x-15=0 | | (3+5i)(5-3i)= | | -15m+9m=0 | | (5x+1)=2 | | -2(8-5)= | | 5(3x-200)+8=418 | | 3y+2(-14)=2 | | 6y+2=2(y-1) | | 2ln(2x)=-4 | | 3(3x+-6)=18 | | 3y+2(1)=2 | | 6x^2+2x-k=0 | | 1.8(5y+64)=1.4(20+2y) | | -8*5+b=300 | | 4(a+2)=14-2(3-29) |